Developing sustainable farmer-to-farmer extension: Experiences from the volunteer farmer–trainer approach in Kenya - Kiptot, Evelyne; Franzel, Steven (Taylor and Francis, 2019)
The reform of agricultural extension institutions in developing countries has in the past decade seen the implementation of many donor-supported farmer-to-farmer extension (F2FE) programs that are participatory and client-oriented. Their effectiveness in disseminating agricultural information is widely documented. However, most of these F2FE approaches only survive as long as funding support continues. Scant information exists on what can make externally initiated F2FE approaches sustainable. Drawing on lessons from a F2FE program known as the volunteer farmer–trainer (VFT) approach in an externally funded project in Kenya, this paper examines what makes such programs sustainable. The findings are based on the experiences of four dairy producer organizations (POs) that, three years after the end of project support, still had strong VFT programs. The paper highlights the importance of four drivers of sustainability: local institutional support, social capital, technical backstopping and motivation of farmer trainers to work voluntarily. Strong POs and farmer groups, coupled with the existence of an informal, multi-institutional network that supported the creation of knowledge and learning processes were key components contributing to the sustainability of the VFT program.